The Antarctic Peninsula Under a 1.5°C Global Warming Scenario - Siegert, Martin; Atkinson, Angus; Banwell, Alison; Brandon, Mark; Convey, Peter; Davies, Bethan; Downie, Rod; Edwards, Tamsin; Hubbard, Bryn; Marshall, Gareth; Rogelj, Joeri; Rumble, Jane; et al. (Frontiers in Environmental Science, 2019)
Warming of the Antarctic Peninsula in the latter half of the 20th century was greater than any other terrestrial environment in the Southern Hemisphere, and obvious cryospheric and biological consequences have been observed. Under a global 1.5°C scenario, warming in the Antarctic Peninsula is likely increase the number of days above 0°C, with up to 130 of such days each year in the northern Peninsula. Ocean turbulence will increase, making the circumpolar deep water (CDW) both warmer and shallower, delivering heat to the sea surface and to coastal margins. Thinning and recession of marine margins of glaciers and ice caps is expected to accelerate to terrestrial limits, increasing iceberg production, after which glacier retreat may slow on land. Ice shelves will experience continued increase in meltwater production and consequent structural change, but not imminent regional collapses. Marine biota can respond in multiple ways to climatic changes, with effects complicated by past resource extraction activities. Southward distribution shifts have been observed in multiple taxa during the last century and these are likely to continue. Exposed (ice free) terrestrial areas will expand, providing new habitats for native and non-native organisms, but with a potential loss of genetic diversity. While native terrestrial biota are likely to benefit from modest warming, the greatest threat to native biodiversity is from non-native terrestrial species.